1993
DOI: 10.1016/0014-5793(93)81772-r
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐linking of a synthetic partial‐length (1–28) peptide of the Alzheimer β/A4 amyloid protein by transglutaminase

Abstract: Cerebral deposits of iliA4 amyloid protein is a pathologic sign of Alzheimer's disease. A synthetic partial-length (I 28) peptide of this protein contains one glutamine and two lysine residues. Here we show that this peptide can be a substrate oftransglutaminase, which catalyzes cross-linking between glutamine and lysine residues in peptides, by demonstrating the formation of multimeric peptides due to the action of this enzyme. A modified (Lys 2s to L-norleucine) version of the synthetic peptide was also cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 27 publications
3
50
1
Order By: Relevance
“…The present results are in general agreement with the recent finding that a partial-length (l-28) /?A4 peptide is a substrate for TG [26]. Whether Lys16 and/or Lys" participate in the cross-linking of /?A4 remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present results are in general agreement with the recent finding that a partial-length (l-28) /?A4 peptide is a substrate for TG [26]. Whether Lys16 and/or Lys" participate in the cross-linking of /?A4 remains to be elucidated.…”
Section: Discussionsupporting
confidence: 93%
“…Whether Lys16 and/or Lys" participate in the cross-linking of /?A4 remains to be elucidated. By using two modified versions of the partiallength /?A4 peptide (Lys16 or Lys2' replaced by L-norleutine) Ikura et al [26] found that Lys16 was involved exclusively in the polymerization. However, exclusion of Lys2* as a potential donor site is questionable, since this amino acid is positioned C-terminal in the partial-length peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme specifically crosslinks Gln 15 and Lys 16 of A␤ but never involves Lys 28 (70), suggesting that Gln 15 and Lys 16 are proximate in an aggregated form of A␤. For our experiments, we synthesized a 26-aa peptide, comprising residues 10-35 of the A␤ peptide (A␤ (10-35) , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The decision of where to place these labels was aided by studies of tissue transglutaminase (tTg) crosslinking of A␤ (66)(67)(68)(69)(70). This enzyme specifically crosslinks Gln 15 and Lys 16 of A␤ but never involves Lys 28 (70), suggesting that Gln 15 and Lys 16 are proximate in an aggregated form of A␤.…”
Section: Resultsmentioning
confidence: 99%